2009
DOI: 10.1111/j.1469-8749.2008.03242.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in movement skills of children with autistic spectrum disorders

Abstract: Aim  We undertook this study to explore the degree of impairment in movement skills in children with autistic spectrum disorders (ASD) and a wide IQ range. Method  Movement skills were measured using the Movement Assessment Battery for Children (M‐ABC) in a large, well defined, population‐derived group of children (n=101: 89 males,12 females; mean age 11y 4mo, SD 10mo; range 10y–14y 3mo) with childhood autism and broader ASD and a wide range of IQ scores. Additionally, we tested whether a parent‐completed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

34
406
3
26

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 564 publications
(469 citation statements)
references
References 23 publications
34
406
3
26
Order By: Relevance
“…Green et al [2009] used a standardised motor battery, the Movement ABC [Henderson & Sugden, 1992], in a large, populationderived study of school-aged children with childhood autism and broader ASD, and found that 79% of the children with an ASD had definite motor impairments with a further 10% having borderline problems. Children with childhood autism (who had a lower average IQ) were more impaired than children with broader ASD, and children with an IQ of less than 70 were almost universally impaired in contrast to two-thirds of the children with an IQ of more than 70.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al [2009] used a standardised motor battery, the Movement ABC [Henderson & Sugden, 1992], in a large, populationderived study of school-aged children with childhood autism and broader ASD, and found that 79% of the children with an ASD had definite motor impairments with a further 10% having borderline problems. Children with childhood autism (who had a lower average IQ) were more impaired than children with broader ASD, and children with an IQ of less than 70 were almost universally impaired in contrast to two-thirds of the children with an IQ of more than 70.…”
Section: Introductionmentioning
confidence: 99%
“…A risk with these studies is that the validity of their findings relies on initial, accurate categorization of participants; the lack of differentiation between AS and HFA, in the case of Manjiviona and Prior (1995), is likely to reflect invalid categorization based on the diagnostic manuals of the time. Some studies find greater motor deficits in individuals with HFA than those with AS (Behere, Shahani, Noggle, & Dean, 2012;Ghaziuddin & Butler, 1998;Green et al, 2009;Papadopoulos et al, 2012;Rinehart, Bellgrove, et al, 2006), others find the opposite picture (Iwanaga, Kawasaki, & Tsuchida, 2000), some find deficits of different types in both groups (Rinehart et al, 2001), and some find no statistical difference between groups (Jansiewicz et al, 2006;Noterdaeme, Mildenberger, Minow, & Amorosa, 2002). Some of these studies have very small samples (Behere et al, 2012;Ghaziuddin & Butler, 1998;Iwanaga et al, 2000;Rinehart, Bellgrove, et al, 2006;Rinehart et al, 2001), casting doubt on their findings.…”
mentioning
confidence: 99%
“…Many studies addressed this question with movement assessment batteries with normative percentiles for performance and objective scoring: for example, the PANESS (Dowell et al, 2009;Dziuk et al, 2007;Floris et al, 2016;Jansiewicz et al, 2006;Mostofsky, Burgess, & Gidley Larson, 2007), the M-ABC or M-ABC2 (Ament et al, 2015;Green, Baird et al, 2002;Green, Moore, & Reilly, 2002;Green et al, 2009;Hanaie et al, 2013;Hanaie et al, 2014;Kopp, Beckung, & Gillberg, 2010;McPhillips, Finlay, Bejerot, & Hanley, 2014;Miyahara et al, 1997;Sumner et al, 2016;Whyatt & Craig, 2012), or the Bruininks-Oseretsky test (Dewey et al, 2007;Ghaziuddin & Butler, 1998;Hilton, Zhang, Whilte, Klohr, & Constantino, 2012;Pan, 2014). These measures yield total scores which were sometimes analysed alone, but they each assess a range of fine and gross motor skills, including balance and gait, hopping or jumping, repetitive sequential movements of the hands and feet, manual dexterity and ball skills (catching and throwing).…”
mentioning
confidence: 99%
See 2 more Smart Citations